Burnout among VET pathway university students: The role of academic stress and school-life satisfaction - Qing Xia; Chunmin Pang; Wenyu Zeng; Qiujing Li; Shiyong Wu; Xiaoma Xiao (BMC Public Health)
Abstract Student burnout has been widely discussed in scholarly and empirical communities. However, little attention has been given to the population of vocational education and training (VET) pathway university students. This cross-sectional study employed partial least squares structural equation modeling (PLS-SEM) to assess the burnout symptoms of Chinese VET pathway university students and their associations with academic stress and school-life satisfaction via the most up-to-date burnout assessment tool (BAT). 357 VET route university students were included in the present study, and the data were analyzed via SPSS 26, PROCESS 4.0, SmartPLS 3, and AMOS 26. The findings revealed that academic stress was positively correlated with student burnout symptoms and significantly negatively correlated with school-life satisfaction. School-life satisfaction partially mediated the association between academic stress and burnout. Institutions and teachers are encouraged to alleviate burnout by relieving vocational education students’ academic stress and increasing their satisfaction with life on campus.